Pengaruh Pemberian Ransum Mengandung Cacahan Eceng Gondok (Eichhornia crassipes) Kering terhadap Kualitas Karkas dan Non Karkas Entog (Cairina moschata) Jantan - Hildan Septian; Dini Widianingrum; Ulfa Indah Laela Rahmah (Tropical Livestock Science Journal, 2026)
This research aims to determine the effect of feeding dry water hyacinth (CEGK) on the quality of carcass and non-carcass Muscovy male ducks, as well as determining the appropriate level of CEGK inclusion. The study used a Completely Randomized Design (CRD) with four levels of CEGK inclusion: 0% (control), 5%, 10%, and 15%, each with five replications. The variables observed included live weight, slaughter weight, carcass weight, carcass percentage, weight without feathers, main parts of the carcass (breast, thighs, wings, back), and non-carcass parts (head, neck, feathers, blood, entrails, feet). Ducks are slaughtered at 145 days of age. Analysis of variance (ANOVA) showed that CEGK supplementation had a significant effect (P<0.05) on live weight and weight without feathers, but had no significant effect (P>0.05) on slaughter weight, carcass weight, carcass percentage, main parts of the carcass, or non-carcass parts. The highest live weight was achieved at an inclusion level of 15% (1700 g), followed by 10% (1663 g), while the highest weight without feathers was also at 15% (1555 g). Although live weight is highest at 15%, an inclusion rate of 10% is recommended as it shows better feed efficiency and a relatively higher carcass percentage trend than 15%, thereby providing an optimal balance between growth performance and carcass quality and supporting the economical use of local feed sources.